DETERMINATION OPTIMUM SITES FOR SOLAR ENERGY HARVESTING IN IRAQ USING MULTI-CRITERIA - Rusol. I. A.; Y. K. Al-Timimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate the multi-criteria Analysis based on the geographic information systems (GIS) to determine the most suitable spatial locations for harvesting solar energy in Iraq. Some of the required criteria and conditions, whether technical, environmental, or economic criteria, have been used. In order to identify the suitability of different regions, 6 defined criteria, including solar radiation, distance from power transmission lines, distance from major roads, distance from residential area, elevation, slope, and land use, are identified. The final map of priority of different locations of Iraq for solar energy harvesting is then created by stacking these criteria layers. It has been found that the entire region is almost suitable for solar energy harvesting with varying suitability index. Moreover, areas of high suitability index cover 14% of the all-area, which is a significant indicator of the potential of solar energy harvesting in Iraq. the area with a moderate suitability index covers 60%, and the low suitability index was 21%, while 5% of unsuitable have been identified. The results indicated that the optimal locations of suitable harvesting solar energy located almost in the south of Iraq.